Development of E-Module Learning for Physical Education Sports and Health for Pencak Silat Material for Students in Junior High Schools - Rahmadani, Mezi Aulia; Khairuddin, Khairuddin; Ihsan, Nurul; Putra, Aldo Naza (Journal of Physical Education Health and Sport, 2023)
The purpose of this study was to develop an E-Module for Learning Physical Education Sports and Health for Pencak Silat Material in Junior High School Students to find out the effectiveness of using the e-module in improving students' skills and physical fitness. This research was carried out using a development research design by adopting the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The results obtained through this study are as follows. 1) This research produced an e-module learning Pencak Silat based on physical fitness training activities for class VII students consisting of cover, introduction, learning and evaluation. 2). Based on the results of limited field tests by experts, the Pencak Silat learning e-module based on Physical Fitness training activities as teaching material for Pencak Silat material for class VII students was declared very feasible to use as teaching material. 3) The effectiveness of using the pencak silat e-module based on class VII physical fitness activities obtained limited field trial data by students of 86.36% strongly agree